Acclimation of Chlamydomonas reinhardtii to extremely strong light - Virtanen Olli; Khorobrykh Sergey; Tyystjärvi Esa (Springer, 2022)
Most photosynthetic organisms are sensitive to very high light, although acclimation mechanisms enable them to deal with exposure to strong light up to a point. Here we show that cultures of wild-type Chlamydomonas reinhardtii strain cc124, when exposed to photosynthetic photon flux density 3000 μmol m−2 s−1 for a couple of days, are able to suddenly attain the ability to grow and thrive. We compared the phenotypes of control cells and cells acclimated to this extreme light (EL). The results suggest that genetic or epigenetic variation, developing during maintenance of the population in moderate light, contributes to the acclimation capability. EL acclimation was associated with a high carotenoid-to-chlorophyll ratio and slowed down PSII charge recombination reactions, probably by affecting the pre-exponential Arrhenius factor of the rate constant. In agreement with these findings, EL acclimated cells showed only one tenth of the 1O2 level of control cells. In spite of low 1O2 levels, the rate of the damaging reaction of PSII photoinhibition was similar in EL acclimated and control cells. Furthermore, EL acclimation was associated with slow PSII electron transfer to artificial quinone acceptors. The data show that ability to grow and thrive in extremely strong light is not restricted to photoinhibition-resistant organisms such as Chlorella ohadii or to high-light tolerant mutants, but a wild-type strain of a common model microalga has this ability as well.